Non-linear triple product A*B - B*A derivations on *-algebras - Mohammad Shavandi; Ali Taghavi (Surveys in Mathematics and its Applications, 2024)
Let 𝒜 be a unital prime *-algebra that possesses a nontrivial projection, and let Φ : 𝒜 → 𝒜 be a non-linear map which satisfies